Digital communication : towards a smart and secure future internet : 28th International Tyrrhenian Workshop, TIWDC 2017, Palermo, Italy, September 18-20, 2017, Proceedings /: towards a smart and secure future internet : 28th International Tyrrhenian Workshop, TIWDC 2017, Palermo, Italy, September 18-20, 2017, Proceedings. (2017) - Unknown
No abstract available